(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article systematically covers the stages of speech development in early childhood. The article describes in detail the gradual formation of speech in the period from 0 to 3 years, the stages of growth of infants from the moment of sound production to the first meaningful words.